2012
DOI: 10.1093/nar/gkr1263
|View full text |Cite
|
Sign up to set email alerts
|

Structural bias in T4 RNA ligase-mediated 3′-adapter ligation

Abstract: T4 RNA ligases are commonly used to attach adapters to RNAs, but large differences in ligation efficiency make detection and quantitation problematic. We developed a ligation selection strategy using random RNAs in combination with high-throughput sequencing to gain insight into the differences in efficiency of ligating pre-adenylated DNA adapters to RNA 3′-ends. After analyzing biases in RNA sequence, secondary structure and RNA-adapter cofold structure, we conclude that T4 RNA ligases do not show significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(214 citation statements)
references
References 45 publications
10
195
4
Order By: Relevance
“…Our data confirmed the strong sequence and/or structural-fold preference of RNA ligases ultimately leading to 3'-or 5'-adaptor-dependent miRNA profiles [20]. To solve this problem and allow a more accurate measurement of the absolute expression level of miRNA, a strategy had been proposed using pools of adaptors degenerated at their first positions [8] [17] [18] [20]. However, this cannot be sufficient to achieve the "true" miRNome characterization as we reported that profiles recovered with a family of barcoded adaptors displayed variation far below the variation observed between adaptors differing over their entire length for a large number of miRNAs (personal data).…”
Section: Second Challenge: Micrornas Of Low Expressionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our data confirmed the strong sequence and/or structural-fold preference of RNA ligases ultimately leading to 3'-or 5'-adaptor-dependent miRNA profiles [20]. To solve this problem and allow a more accurate measurement of the absolute expression level of miRNA, a strategy had been proposed using pools of adaptors degenerated at their first positions [8] [17] [18] [20]. However, this cannot be sufficient to achieve the "true" miRNome characterization as we reported that profiles recovered with a family of barcoded adaptors displayed variation far below the variation observed between adaptors differing over their entire length for a large number of miRNAs (personal data).…”
Section: Second Challenge: Micrornas Of Low Expressionsupporting
confidence: 77%
“…Four categories of miRNAs can be detected according to expression fold changes: 1 to 3, 3 to 10, 10 to 50, and beyond. Our data confirmed the strong sequence and/or structural-fold preference of RNA ligases ultimately leading to 3'-or 5'-adaptor-dependent miRNA profiles [20]. To solve this problem and allow a more accurate measurement of the absolute expression level of miRNA, a strategy had been proposed using pools of adaptors degenerated at their first positions [8] [17] [18] [20].…”
Section: Second Challenge: Micrornas Of Low Expressionsupporting
confidence: 52%
“…This effect may be further strengthened by spontaneous hydrolysis of 5 ′ triphosphate RNA ends during the ligation step of the PSS-adaptor and preceding RNA treatments, generating 5 ′ ends opened for ligation. On the other hand, the first step of the tagging procedure using the T4 RNA ligase is certainly not complete and acts with different efficiency on different RNA molecules (Zhuang et al 2012;Raabe et al 2014). Therefore, at the second ligation step, 5 ′ monophosphate ends (i.e., PSSs) that have escaped the first tag can be ligated to the TSS-adaptor and appear as false TSSs.…”
Section: Annotated Genes 769663 1992494mentioning
confidence: 99%
“…The Illumina Small RNA Kit uses adapters that target small ncRNAs, such as miRNAs and snoRNAs, with 5 ′ monophosphate and 3 ′ OH termini (Illumina product literature) followed by size-selection of cDNAs prior to sequencing. This and similar methods using sequential RNA-seq adapter ligation are typically time consuming, have well-documented sequence and secondary structure biases, and can yield undesirable side products (Hafner et al 2011;Zhuang et al 2012;Raabe et al 2014).…”
Section: Introductionmentioning
confidence: 99%